“Sistema de control interno para la empresa Provelectric del cantón La Maná provincia de Cotopaxi, año 2019”. - Guerra Corrales, Karen Yesenia (2020)
The objective of this project was to design an internal control system in the Provelectric company, in order to maintain an adequate control of its activities through policies and procedures allowing staff to unwrap properly within their functions. It also helped to maximize profits and minimize the risks, avoiding suffering economic losses and the resources are aimed at the benefit of the company and the information it has is real. With the absence of a well-structured internal control system, it did not allow the company to work correctly to achieve the goals and objectives, not being able to maintain an adequate control of staff activities and having as a problem the loss of resources and fraud at the time of recording both financial, accounting and administrative information. For the realization of this project, methods and techniques were used that allowed the collection of information efficiently through an interview with the manager and an internal control evaluation that facilitated the detection of existing problems, and an interview with employees in order to use the SWOT analysis which allowed us to identify strengths related to the quality and variety of materials offered, as well as weaknesses regarding the absence of training for employees based on internal control, lack of a manual of functions, policies and procedures. The result obtained was to know the level of risk facing the Provelectric company through an internal control evaluation of the areas. The input of this project was to prepare a manual that contains functions, policies and procedures for the proper development of activities, improving the operational processes of each area, achieving the goals and objectives. This project was important because through an internal control system the company had a control of the operations, obtaining reliability in the information fully complying with the policies applied. The impact that this project had was social and economic because it achieved the satisfaction of the clients, obtaining profits in the sales made and the beneficiary of this project was not simply the owner but also the staff that works since through this system evaluates the performance of each employee.